Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay (Studi Empiris Pada Perusahaan Real Estate Dan Property Yang Terdaftar Di Bei Periode 2013-2015) - Ramadhan, Irfan; , Dra. Nursiam, M.H., Ak., CA (2017)
This research attempts to analyzing the factors that affect an audit delay to a company of real estate and property listed on the Indonesian Stock Exchange the period 2013-2015. The factors that the tested in this research is an audit opinion, profitability, liquidity, and size of the company as the independent variable, while an audit delay as the dependent variable. The population research this is a company of real estate and property listed on the Indonesian Stock Exchange the period 2013-2015. Sampling technique employed in this research is purposive sampling wuth the criteria which had been determined. The total sample collected 123 companies as much as. The data analysis using multiple linear regression. The result of the research shows that an audit opinion, profitability, and liquidity have had a positive impact on an audit delay, while size of the company have a negative impact on an audit delay